Peningkatan Apresiasi Tari Nusantara Melalui Model Blended Learning di Sekolah Menengah Pertama - Rusnia Yanti; Juju Masunah (Universitas Negeri Medan, 2021)
This research is aimed to improve knowledge, attitude, skill and appreciation of Nusantara Dances. It is conducted by Action Research method which is developed by Kemmis & McTaggart. The data were collected by questionnaire and analysed by Mix method which is developed by Creswell. The sample of this research is the 8th grade students of Public Junior High School 2 Kotabaru. Knowledge, attitude and skill of appreciation of Nusantara dances is important to be delivered to junior high school student as one of provision effort to nusantara culture, especially dances. The Learning of Nusantara Dances Appreciation is implemented through two cycles. Each cycle has four meetings. Before the intervention action of first cycle, there is a Pre-test. And then the final post test result of first Cycle shows that there is improvement result compared to the pre-test result. More over the post test result of second cycle is imporoved too compared to the post test result of the first cycle, even it has reached the set out target. In conclusion according to the result of the research, Blended learning model is effective to be used on improving the appreciation of Nusantara Dances. Thus, Art & Culture Teacher at school is suggested to use this blended learning model.